New challenges in regional development - the role of regional institutions - Veronika Gaube; Sabine Sedlacek (European Regional Science Association (ERSA), 2003)
The paper is based on an institutional survey in Austria. The aim of the survey was to identify different types of regional institutions - traditional versus new innovative institutions. The main research focus concentrated on new challenges in regional development processes resulting from the EU-strategy to foster sustainable regional development in the member states. As a consequence the question of the relevance of completely new types of institutions arises on the one hand. These new types are directly linked to the EU structural fund policy, e.g. LEADER+ manager, EU regional manager. With respect to this focus these institutions mainly concentrate on EU programmes and initiatives. On the other hand the traditional institutions have their specific focus on e.g. tourism, economic development etc. not necessarily with any direct link to EU-programmes. Therefore this contribution starts with a general institutional analysis (i.e. organisational attributes, activity profiles, regional embeddedness, position in the regional stakeholder network, etc.) to find differences between traditional and new innovative institutions. Based on these attributes we will present the institutional landscape in Austrian regions. This landscape consists of the above mentioned traditional and the new innovative institutions. Are these co-existing institutions able to concentrate the top-down (i.e. regional policy) and the bottom-up (i.e. project initiatives) interests in order to foster sustainable regional initiatives' For answering this question we haven chosen several case-studies in different Austrian regions. This case study analysis will be presented as follows: * Strengths and weaknesses of different institutional settings (e.g. various competing institutions versus one strong institution) * Comparison of strategic decisions in the case study regions * Is there any ideal solution identifiable for other regions'
Keywords: 330